Electron spin resonance study on Mo SiO2 and Mo TiO2 with adsorbed benzene - Ignatovych, M.; Teslenko, V.; Eremenko, A.; Ogenko, V.; Chuiko, A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2002)
The study is devoted to ESR-investigation of the primary processes upon chemisorption of benzene molecules onto the molybdenum supported on dispersed SiO2 and TiO2 samples. It has been confirmed that benzene chemisorption onto the Mo6+ species results in one-electron transfer in the ground state and paramagnetic species formation, namely reduced molybdenum species (Mo5+ species) and radicals of benzene. Computer treatment of ESR experimental data revealed that there are several types of Mo5+ species and benzene radicals, the assignment of which is proposed.